The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/20420986221100117
|View full text |Cite
|
Sign up to set email alerts
|

The patterns and implications of potentially suboptimal medicine regimens among older adults: a narrative review

Abstract: In the context of an ageing population, the burden of disease and medicine use is also expected to increase. As such, medicine safety and preventing avoidable medicine-related harm are major public health concerns, requiring further research. Potentially suboptimal medicine regimens is an umbrella term that captures a range of indicators that may increase the risk of medicine-related harm, including polypharmacy, underprescribing and high-risk prescribing, such as prescribing potentially inappropriate medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Under-prescribing is another reason for a potentially suboptimal medication regime [ 32 ]. We observed a higher number of patients with PAD in the post-intervention group were discharged on antiplatelet agent and lipid-lowering therapy following implementation of the geriatric co-management model.…”
Section: Discussionmentioning
confidence: 99%
“…Under-prescribing is another reason for a potentially suboptimal medication regime [ 32 ]. We observed a higher number of patients with PAD in the post-intervention group were discharged on antiplatelet agent and lipid-lowering therapy following implementation of the geriatric co-management model.…”
Section: Discussionmentioning
confidence: 99%
“…with poorer clinical outcomes [2]. Socioeconomic disadvantage, beliefs, and health literacy can contribute to nonadherence or suboptimal prescribing.…”
Section: Suboptimal Prescribing Of Medicines Has Been Associatedmentioning
confidence: 99%
“…Polypharmacy and hyperpolypharmacy were defined as the use of five or more; and ten or more medicines, respectively [2]. PIMs were assessed using the Beers 2015…”
Section: Definitionsmentioning
confidence: 99%
“…Numerous previous studies have used several of the PIM and PPO tools used in this study to examine the PIM and/or PPO prevalence in different settings. According to a recent review of PIM prevalence studies [6], the proportions of study participants affected by PIMs was 44.3% for FORTA (vs. 76.5% in this study) and ranged from 26.7% to 67.3% for STOPP (vs. 65.9% in this study), from 37.5% to 90.6% for EU(7) PIM (vs. 61.9% in this study) and from 13.7% to 68.5% for PRISCUS (vs. 12.8% in this study). Campbell et al (2010) found that 10.8% of a sample of African American adults aged ≥ 70 years were exposed to at least one drug with strong anticholinergic properties (vs. 6.6% in this study) [29,30].…”
Section: Comparison To Literaturementioning
confidence: 99%
“…As a guidance for clinicians, a number of consensus-based instruments have been developed listing potentially inappropriate medication (PIM) to be avoided or used with caution in older people. Instruments alerting physicians to potential prescribing omissions (PPO) have also been developed [6][7][8]. Internationally prominent examples include START/STOPP criteria, and EU(7)-PIM, while the PRISCUS and FORTA lists are German developments [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%